Coleções de passagem: o processo de construção de coleções pessoais a partir da análise de acervo do colecionador Milton Ferreira - Fernanda Cecilia Campos Coimbra (2018)
The study consists in the analysis of the process by construction of collections and self archivation, with the objective of study the house of the collector Milton Ferreira, located in the interior of the city of Arcos, in Minas Gerais - Brazil. The house shelter many collections related to the personal memory of the collector, reffering too a colletive familiar memory and of the residents of him hometown, Arcos. Walking by the house, wesee objects full by memories. Milton Ferreira abuses in the amount, using a giant variety of materials and images. It is possible to identify littles collections, for example, of clocks, knifes, tools, pans, photographs and others that, end diluted in a big personal collection. The attention of the viewer it is lost by trying to identify all the details and the view passesby like in the set. But, the accumulation of objects, in a way, does not depersonalize the ambient, it stays appearing and existing like a home, having always balance by the collections and the space. By the action of extracting objects and images of them contexts, it is possible to see that the collector proposes, in a unconscious way, a new logic to this objects and images, exposing them collections in the walls and ceiling of the house. The pertinent questions by the memory are evident in the work of the collector, specifically in the relation that produces in the memory of the accumulation. In this way, this search intents to investigate the process of construction of the collections in the house of Milton ferreira, whit the intent of create a dialogue with works of contemporary art that, by the collections, bring to front like thematic, the archive and the forgetfulness. Have like a goal propose a dialogue by the old cabinets of curiosities andthe archive of Milton ferreira and other collectors and contemporary artists, intending to present the relations proposed by the process of analises of the personal collections of Milton Ferreira and the contemporary context of arts. It intents too propose new reflectionsby the necessity of construct personal collections and amplify the debate in relation of the concept of art and how happens the reception of a object with normal use like a work of art.